Population and habitat analysis of Javan gibbon (Hylobates moloch) in fragmented forests of West Java, Indonesia - ZAMZAM I’LANUL ANWAR ATSAURY; TEGUH HUSODO; ERRI NOVIAR MEGANTARA; TIEN LASTINI; ENDANG HERNAWAN; INDRI WULANDARI; SYA SYA SHANIDA (Society for Indonesian Biodiversity, 2025)
Abstract. Atsaury ZIA, Husodo T, Megantara EN, Lastini T, Hernawan E, Wulandari I, Shanida SS. 2025. Population and habitat analysis of Javan gibbon (Hylobates moloch) in fragmented forests of West Java, Indonesia. Biodiversitas 26: 2857-2872. Javan gibbons (Hylobates moloch) face various anthropogenic disturbances that are intensive enough to damage and even eliminate their habitat. Additionally, previous studies have primarily focused on protected areas. However, there is limited information on the Javan gibbon in non-conserved areas, such as Ciletuh Geopark, Cisokan, Cijedil, and Kanaan, West Java, Indonesia. The study objective was to determine the distribution and habitat of Javan gibbon in non-conservation areas in West Java. Line transect distance sampling and quarter methods were used in this study. Despite the high level of anthropogenic disturbance, Cisokan exhibited the highest density of Javan gibbon individuals and groups, with 19.48 individuals per square kilometer and 7.79 groups per square kilometer. Generally, the habitat of Javan gibbons is dominated by food plants, such as kondang (Ficus variegata), puspa (Schima wallichii), and beunying (Ficus fistulosa). Hence, 97 plant species were identified as food plants of Javan gibbons, while 84 were eaten by their fruits, 25 by their leaves, and 12 by both. Javan gibbons tend to live in forests with closed and interconnected canopies, as well as on slopes and hilltops with a slope greater than 40% at altitudes ranging from 115 to 1,564 meters above sea level (m asl). Establishing ecological corridors to enhance habitat connectivity in degraded vegetation is crucial for conserving Javan gibbon populations.